Qualitative focus group study investigating experiences of accessing and engaging with social care services: perspectives of carers from diverse ethnic groups caring for stroke survivors - Geoffrey Cloud; Nan Greenwood; Jess Holley; Theresa Ellmers; Gill Mein (BMJ Open)
Objectives Informal carers, often family members, play a vital role in supporting stroke survivors with post-stroke disability. As populations age, numbers of carers overall and those from minority ethnic groups in particular, are rising. Carers from all ethnic groups, but especially those from black and minority ethnic groups frequently fail to access support services, making understanding their experiences important. The study therefore explored the experiences of carers of stroke survivors aged 45+ years from 5 ethnic groups in accessing and receiving social care services after hospital discharge.Design This qualitative study used 7 recorded focus groups with informal carers of stroke survivors. Data were analysed thematically focusing on similarities and differences between ethnic groups.Setting Carers were recruited from voluntary sector organisations supporting carers, stroke survivors and black and minority ethnic groups in the UK.Participants 41 carers from 5 ethnic groups (Asian Indian, Asian Pakistani, black African, black Caribbean, white British) participated in the focus groups.Results Several interconnected themes were identified including: the service gap between hospital discharge and home; carers as the best person to care and cultural aspects of caring and using services. Many themes were common to all the included ethnic groups but some related to specific groups.Conclusions Across ethnic groups there were many similarities in the experiences of people caring for stroke survivors with complex, long-term care needs. Accessing services demands effort and persistence on carers’ part. If carers believe services are unsatisfactory or that they, rather than formal services, should be providing support for stroke survivors, they are unlikely to persist in their efforts. Cultural and language differences add to the challenges black and minority ethnic group carers face.